Inflicted head injury in a child masquerading as child abuse - Agrawal, Amit (Indian Journal of Neurotrauma, 2012)
In low- and middle-income countries childhood injuries and violence becoming a significant and growing cause of child death and disability and in spite of its significance, the issue of childhood injuries and violence has been only minimally addressed. We present an unusual case of head injury in a child where the child was hit by her fellow colleague, and the lesions were masquerading the injuries of child abuse. Although it was difficult to find out the exact motive, probably it was an act of non-deliberate injury. However an early onset of delinquency can increase the risk of later serious, violent, and chronic offending, hence further research is needed specifically on juvenile violence.
Keywords: Non-accidental head injuries; Head injury; Inflicted head injury; Child abuse